Who Ought to Be Sentenced to Death and Why?: Reasons and Legal Justifications of the Death Penalty in the Book of Judith - Korytiaková, Martina (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2026)
The paper primarily scrutinises the death penalty of Holofernes in terms of its reasons, legal justification, and the way of its realisation in the Judith story. The study further reveals the identity of other narrative characters who faced the threat of capital punishment and inquires into the grounds for their announced punishment by death. It is demonstrated that death punishments in the story—be they realised or just planned—relate to a specific capital offence according to the Torah. Holofernes’ capital penalty is exceptional as justified by two reasons. The sanction to death of Achior is, in turn, unique as it allows for an interpretation based on the biblical as well as Greek parallels. For the ironic purposes the sentence to death for a capital offence as ordered by the Jewish legal system is issued in the story by the gentiles in respect to the others, the Israelites included.